Pleural Effusion Caused by Mycolicibacterium mageritense in an Immunocompetent Host: A Case Report - Niitsu, Takayuki; Kuge, Tomoki; Fukushima, Kiyoharu; Matsumoto, Yuki; Abe, Yuko; Okamoto, Masashi; Haduki, Kako; Saito, Haruko; Nitta, Tadayoshi; Kawano, Akira; Matsuki, Takanori; Motooka, Daisuke; et al. (Frontiers in Medicine, 2021)
Mycolicibacterium mageritense (M. mageritense) is a rare species among rapidly growing mycobacteria, and M. mageritense pleurisy is very rare. Here, we report for the first time, an immunocompetent patient with pleurisy caused by M. mageritense. The patient had no history of immunodeficiency and no recurrence of lung cancer after surgery. However, 8 months after surgery, he developed a new lung shadow and pleurisy. Although whole-genome analysis of the colony cultured from the patient's pleural fluid revealed M. mageritense, we could not identify it in time, resulting in a poor outcome. M. mageritense pleurisy in this case might have occurred via a bulla rupture of the lung lesion because computed tomography of the patient's chest showed pneumothorax and a lung lesion in contact with thoracic cavity. This case emphasized that nontuberculous mycobacterial pleurisy should be considered in the differential diagnoses of pleural effusion even in immunocompetent patients. Advancement of comprehensive and rapid analyses of genomic data from clinical specimens will lead to better treatment strategies.